Transarterial Chemoembolization Combined With Endoscopic Therapy Is Beneficial for Unresectable Hepatocellular Carcinoma With Esophagogastric Varices - Tao, Ziwen; Ruan, Yuying; Peng, Zhi; Zhang, Kai; Gao, Yanjing (Frontiers in Oncology, 2021)
Background: The efficacy of transarterial chemoembolization (TACE) combined with endoscopic therapy for unresectable hepatocellular carcinoma with esophagogastric varices remains unclear. Methods: The study has been registered on ClinicalTrials.gov with the number of NCT05017922 (https://register.clinicaltrials.gov). Eligible patients were divided into combined group (received TACE plus endoscopic therapy) and control group (only received TACE). The occurrence of death and bleeding episodes during the follow-up were recorded. Kaplan-Meier analysis was used to compare outcomes between the two groups. Cox proportional hazard model was used to determine independent predictors for the survival. Results: 89 patients were included, 42 in the combined group, others in the control group. During the follow-up, 51 patients died, the 1-year, 2-year and 3-year survival rates were 64.9%, 45.5% and 34.5%. The cumulative survival was significantly higher in the combined group than in the control group (p=0.027), the 1-year, 2-year, 3-year survival rates were 75.5%, 55.9%, 43.8% and 55.0%, 35.9%, 26.6%, respectively. 44 patients experienced bleeding, the bleeding rate was significantly higher in the control group than in the combined group (77.4 vs. 56.8%, p=0.016). Multivariate analysis showed that treatment, hemoglobin, portal vein tumor thrombosis, and aspartate aminotransferase were independent predictors for overall survival, the first three factors were also independent predictors for bleeding-free survival. Patients who received primary prophylaxis had longer overall survival (p=0.042) and bleeding-free survival (p=0.029) than those who received secondary prophylaxis. Conclusions: TACE combined with endoscopic therapy significantly improved survival and reduced bleeding rates in unresectable hepatocellular carcinoma with esophagogastric varices patients. Portal vein tumor thrombosis was strong negative prognostic factor for both overall survival and bleeding-free survival. Primary prophylaxis improved survival benefits compared with secondary prophylaxis.